Effects of bifurcation-specific and conventional stents on coronary bifurcation flow. An experimental and numerical study. (21st March 2017) - García García, J.; García Carrascal, P.; Castro Ruiz, F.; Manuel Martín, F.; Fernández, J.A.
Abstract: Our paper builds on existing research into conventional bare metal stents in order to assess new devices specifically designed for coronary bifurcation angioplasty. The first aim is to validate the numerical model against data from in vitro experiments on stented coronary phantoms. A surface mesh was built in accordance with micro-computed tomography images obtained from coronary stents implanted in silicone models and used for numerical analysis. Computational simulations for steady and unsteady cases generally agreed with their experimental counterparts. A second objective is to compare the hemodynamic performance of one of these new devices (Stentys) to that of conventional devices and stenting techniques in a simplified coronary bifurcation model. Four different coronary bifurcation stenting techniques were analyzed. We have focused on factors contributing to restenosis, such as wall shear stress (WSS), oscillatory shear index (OSI), pressure loss, and local normalized helicity (LNH). It was found that bifurcation-specific stents implanted in the side branch led to increased malapposition. This effect has proved to be more important than stent specific design characteristics such as strut size (different for conventional and Stentys stent). This conclusion is confirmed by means of drop in pressure and mechanical energy loss rate calculation; for the latter, the increase ranged from 9% to 17%, depending on the stenting technique, when dedicated stents were implanted in the side branch. The behavior patterns presented in this study should be double-checked against those obtained in more realistic geometries.